2019
DOI: 10.7717/peerj.8035
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome sequencing of Verticillium dahliae from a cotton farm reveals positive correlation between virulence and tolerance of sugar-induced hyperosmosis

Abstract: Verticillium dahliae causes disease symptoms in its host plants; however, due to its rapid variability, V. dahliae is difficult to control. To analyze the reason for this pathogenic differentiation, 22 V. dahliae strains with different virulence were isolated from a cotton farm. The genetic diversity of cotton varieties make cotton cultivars have different Verticillium wilt resistance, so the Xinluzao 7 (susceptible to V. dahliae), Zhongmian 35 (tolerant), and Xinluzao 33 (resistant) were used to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 69 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…Regarding the interaction between V. dahliae and cotton, previous studies have mostly focused on either the pathogen or the host at the early infection stage 20 . In the present study, we found two distinct stages during the molecular interaction through time-course transcriptome analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the interaction between V. dahliae and cotton, previous studies have mostly focused on either the pathogen or the host at the early infection stage 20 . In the present study, we found two distinct stages during the molecular interaction through time-course transcriptome analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the interaction between V. dahliae and cotton, previous studies have mostly focused on either the pathogen or the host at the early infection stage 20 . Here, we found two distinct stages in molecular interaction through a longer-term transcriptome analysis.…”
Section: Discussionmentioning
confidence: 99%